Biolarvasida Nyamuk Berbentuk Powder Dari Biji Pepaya - Cahyani, Meisyenda; Dewi, Dyah Ajeng Apresia Mutiara; Nazullah, Devy Eka; Rianti, Yestyana Mufid; Harianto, Syarifa Candraningtyas; Fadila, Nur Intan; Ashilah, Nafisha Azmi Witya; Rosidah, Siti Khofifatur (UPT Penerbitan Universitas Jember, 2023)
Background: Dengue fever is an infectious disease that is transmitted through mosquito vectors, generally the mosquitoes that carry the dengue hemorrhagic fever virus are the Aedes aegypti and albopictus mosquitoes. The preferred place to live for mosquitoes is an environment with hot and humid weather like Indonesia. Therefore, there is a need for preventive efforts to prevent the breeding of mosquitoes that cause dengue fever. One method that is being developed is the use of biolarvicide from papaya seeds (Carica papaya). Method: Biolarvicide powder is produced from papaya seeds (Carica Papaya L) which are dried for one day until completely dry. Then the powder undergoes an oven process for two hours at a temperature of 38°C. Finally, the powder is crushed again to become a fine powder. Results: After outreach to several respondents from Suci Village, Panti District, Jember Regency, these respondents answered the post-test correctly, but there were several respondents who answered that draining the bathtub was not necessary. Conclusion: With the presence of biolarvicide powder from papaya seeds, it can help the community in dealing with dengue fever which is carried by this mosquito vector.Keywords: aedes aegypti mosquito, larvicide, papaya seeds.